hint the second equation can be factored
What's happening here? 3x−3y=18 >x−y=6> 4x−4y=24
Oh, did you delete your response...?
the objective of the elimination method is to pick a variable and make the coefficients equal and opposite so that will be eliminated when the equivalent equations are added
\(5x+4y=12\) \(3x-3y=18\) > \(x-y=6\) > \(4x-4y=24\) divided times by 6 6 \(5x+4y=12\) \(4x-4y=24\) ~~~~~~~~~ Add the two equations now, and tell me what you get.
I deleted my reply, to modify it....
MISTAKE: Oh, divide by 3, not 6.
correction equation 2 divided by 3
yes, just said that
Oh, I see what you're doing now. Don't you mean multiplied by 4 for the 2nd step?
Then you have to add the equations.
I was taught a different method to solve this though. Are you sure this is a valid way to solve for the elimination method?
yes, I am positive
(good that you noticed my typo errors, thank you)
glad you are paying attention
he choose to get rid of y's now add and solve for x
yes that is the way and I was never in any of his classes
Alright I'll solve for it then! 9x=36 > (9/9)x=(36/9) > x=4
yes, x=4 is right.
And then you plug the value of x into one of the equations to get y. I can understand it from here! Thank you two so much for the help! :)